(untitled) (Conference Zone, 2022)
Children’s age groups are divided into the following classifications: preschoolers up to 3 years old, preschoolers from 3 to 7 years old; junior school age 7 to 11 years. As children develop, their body composition and body proportions and habits and activities of interest in the appearance and nature of movements change. Accordingly, taking into account the psychological-physiological and physical development of children at different ages, the range of children’s clothing will be diverse in terms of its type, structure, color scheme and decoration. In this regard, children’s clothing is designed to suit each age group. The range of clothes for kindergarten girls consists of a variety of dresses, gowns, sundresses, blouses, pants, semi-overalls